Case Report: Endoluminal removal of a conical retrievable superior vena cava filter with a retraction hook attached to the wall - Tian, Xuan; Liu, Jianlong; Li, Jinyong; Liu, Xiao; Zhou, Mi; Tian, Yule (Frontiers in Cardiovascular Medicine, 2024)
We report the case of a 22-year-old male who underwent endoluminal surgery and was implanted an Option Elite filter in the superior vena cava (SVC) while the filter retraction hook was attached to the vessel wall. The patient requested to remove the filter after 155 days. Preoperative ultrasonography and CT examination revealed that the filter retraction hook was very likely to penetrate the SVC wall and its tip was very close to the right pulmonary artery. The SVC was not obstructed, and no thrombus was observed in either upper limb. After the filter retrieval device (ZYLOX, China) failed to capture the filter hook, we introduced a pigtail catheter with its tip partly removed and a loach guidewire, used a modified loop-snare technique to cut the proliferative tissues and free the hook, and finally removed the filter successfully by direct suspension of the guidewire. During this procedure, the patient experienced discomfort, such as chest pain and palpitations, but these symptoms disappeared when procedure completed. Repeated multiangle angiography revealed no contrast medium extravasation, no complications such as pericardial tamponade, pleural effusion, SVC haematoma formation, right pulmonary artery dissecting aneurysm, or intramural haematoma. We initially presented the modified loop-snare technique used to remove a conical superior vena cava filter (SVCF), so this method can be considered a practical and novel auxiliary technique for successful filter retrieval.